Field notes contributed by Jane Clark, spring 1996 - Clark, Janeet al (1996)
Spring report of birds and locations contributed by Jane Clark. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1996. Epson - sheet feed